Impact of Visual Awareness of Postoperative Appearance on Functional Recovery After High Tibial Osteotomy: A Retrospective Case-Control Study - Bayrak, Hünkar Çağdaş; Karagöz, Bekir (The European Research Journal, 2026)
Objective: This study aimed to evaluate the impact of visual awareness of preoperative and postoperative leg appearance on patient satisfaction and functional recovery after medial open-wedge high tibial osteotomy (MOWHTO) in patients with varus malalignment. We hypothesized that providing patients with visual feedback of their cosmetic improvement may enhance perceived functional outcomes and overall satisfaction. Methods: A retrospective case-control study was conducted including 57 patients who underwent MOWHTO for varus malalignment between 2019 and 2023. Patients were divided into two groups: Group 1 (n=24), who were shown preoperative and postoperative leg photographs, and Group 2 (n=33), who were not. Functional outcomes were assessed using the Short Form-36 (SF-36) physical and mental scores and Lysholm score. Radiological parameters and joint range of motion were also evaluated preoperatively and at final follow-up. Results: Both groups showed significant postoperative improvements in SF-36 and Lysholm scores (P<0.05). However, Group 1 demonstrated significantly higher postoperative SF-36 physical (P=0.001), SF-36 mental (P=0.001), and Lysholm scores (P=0.002) compared to Group 2. Although radiological parameters and joint range of motion improved significantly in both groups, there were no significant differences between groups. Conclusion: Visual presentation of preoperative and postoperative leg photographs may increase patient awareness of surgical changes and be associated with improved patient-reported outcomes and satisfaction following MOWHTO. Incorporating visual methods into patient education may present a simple approach to influencing postoperative perception.